Creative Thinking Skills in Colloidal Material of 11th grade Science Students at SMAN 1 Mempawah Hilir - Fitri, Sari Nur; Junanto, Tulus; Sasri, Risya; Hairida, Hairida; Rasmawan, Rahmat (Universitas Pendidikan Mandalika, 2024)
The industrial revolution 4.0 makes us develop into adaptive humans. 21st century skills, that involves thinking critically and inventiveness, abilities to communicate and teamworks, are needed to adapt to all technological changes. Among the four 21st century skills, creative thinking skills are needed to develop innovative ideas in answering problems in the learning process. The variable of this research is students’ creative thinking skills. The aspects studied consist of originality, fluency, flexibility, and elaboration. The research process was conducted with descriptive quantitative using a sample of 35 students of class XI IPA at SMA Negeri 1 Mempawah Hilir. The research instruments used were creative thinking test questions in the form of descriptions and interview guidelines. The results of data analysis stated that students’ creative thinking skills were included in the insufficient category with a percentage of 74,29% of the sample. The average value in originality is 42,68%, while the aspects of fluency, flexibility, and elaboration have the same average of 36,78%. Several factors cause the low level of students’ creative thinking skills; namely students still memorize the material in the book, lack of learning experience, students tend to give answers as they are because they think they will get a score even though they only write a few answers, and another factor is that students lack focus when working on test questions.